The use of gaze to study cognition: limitations, solutions, and applications to animal welfare - Wilson, Vanessa A. D.; Bethell, Emily J.; Nawroth, Christian (Frontiers in Psychology, 2023)
The study of gaze responses, typically using looking time paradigms, has become a popular approach to improving our understanding of cognitive processes in non-verbal individuals. Our interpretation of data derived from these paradigms, however, is constrained by how we conceptually and methodologically approach these problems. In this perspective paper, we outline the application of gaze studies in comparative cognitive and behavioural research and highlight current limitations in the interpretation of commonly used paradigms. Further, we propose potential solutions, including improvements to current experimental approaches, as well as broad-scale benefits of technology and collaboration. Finally, we outline the potential benefits of studying gaze responses from an animal welfare perspective. We advocate the implementation of these proposals across the field of animal behaviour and cognition to aid experimental validity, and further advance our knowledge on a variety of cognitive processes and welfare outcomes.